Subtribal, generic and subgeneric composition of darkling beetles of the tribe Helopini (Coleoptera: Tenebrionidae) in the Eastern Palaearctic - Nabozhenko, Maxim; Ando, Kiyoshi (Acta Zoologica Academiae Scientiarum Hungaricae, 2018)
A review of the following Eastern Palaearctic (China, Russian Far East, Korean Peninsula, Japan and Taiwan) genera of the tribe Helopini (Coleoptera: Tenebrionidae) is given: subtribe Helopina: Nipponohelops Masumoto, Ando et Akita, 2006, Apterotarpela Kaszab, 1954, Catomus Allard, 1876, Stenohelops Reitter, 1922; subtribe Cylindrinotina: Nalassus Mulsant, 1854, and Asialassus gen. n. (type species Helops cordicollis Marseul, 1876). As a result the following combinations and synonymy are proposed (all from the genus Tarpela Bates, 1870): Apterotarpela clypealis (Kaszab, 1954), comb. nov., Apterotarpela subasperipennis (Kaszab, 1954), comb. nov., Nalassus (Nalassus) brunneus brunneus (Marseul, 1876), comb. n., Nalassus (Nalassus) brunneus konoi (Nakane, 1963), comb. n., Nalassus (Nalassus) elegantulus (Lewis, 1894), comb. n., Nalassus (Nalassus) formosanus (Masumoto, 1981), comb. n., Nalassus (Nalassus) akitai (Masumoto, 1998), comb. n., Nalassus (Nalassus) kawabatai (Akita et Masumoto, 2012), comb. n., Nalassus (Nalassus) zoltani (Masumoto, 1981), comb. n., Nalassus (Nalassus) pilushenmuus (Masumoto, Akita and Lee, 2017), comb. n., Nalassus (Nalassus) yuanfengus (Masumoto, Akita et Lee, 2017), comb. n., Nalassus (Nalassus) xiaoxueshanus (Masumoto, Akita et Lee, 2017), comb. n., Nalassus (Nalassus) dongurii (Masumoto, Akita et Lee, 2017), comb. n., Nalassus (Nalassus) merkli (Masumoto, Akita and Lee, 2017), comb. n., Nalassus (Nipponalassus) andoi (Masumoto, 1993), comb. n., Nalassus (Nipponalassus) lewisi (Masumoto, 1993), comb. n., Asialassus cordicollis (Marseul, 1876), comb. n., Asialassus amamiensis (Kaszab, 1964), comb. n., Asialassus kimurai (Masumoto, 1996), comb. n. (= Tarpela tokunoshimana Masumoto et Akita, 2001: 20, syn. n.), Asialassus tsushimanus (Nakane, 1979), comb. n., Asialassus todai (Ando, 2006), comb. n., Asialassus adachii (Akita et Masumoto, 2009), comb. n. A new subgenus of the genus Nalassus is proposed: Nipponalassus subgen. n. (type species Tarpela andoi Masumoto, 1993). Two new species are described from China: Catomus (Sinocatomus) stanislavi sp. n. and Stenohelops (Stenomaleis) chinensis sp. n. Morphological diagnoses and keys are given to subtribes, genera and species.